Pengaruh Corporate Governance terhadap Sustainability Report Disclosure dengan Ukuran Dewan Komisaris Sebagai Variabel Moderasi - Aptada, Cetta; Wahyuningrum, Indah Fajarini Sri (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the effect of corporate governance on sustainability report disclosure with board size as a moderating variable in non-cyclical manufacturing sector companies listed on the Indonesia Stock Exchange for the period 2021-2024. This quantitative research uses secondary data in the form of annual reports and sustainability reports from 32 companies with a total of 128 observations. Data analysis techniques using panel data regression with Random Effect Model selected based on Chow Test, Hausman Test, and Lagrange Multiplier Test. The novelty of this research lies in adding board size moderation variable that examines the role of board size in strengthening or weakening the relationship between corporate governance mechanisms and sustainability reporting quality in the Indonesian context which has only implemented full sustainability reporting obligations since 2021 according to POJK No. 51/POJK.03/2017. The results showed that foreign ownership has no significant effect on sustainability report disclosure (p=0.689>0.05), while majority ownership (p=0.009<0.05) and gender diversity (p=0.000<0.05) have a significant positive effect on sustainability report disclosure. Board size is proven to moderate by strengthening the effect of foreign ownership on sustainability report disclosure (p=0.031<0.05), but does not moderate the effect of majority ownership (p=0.149>0.05) and gender diversity (p=0.423>0.05). Adjusted R-squared value increased from 29.6% in Model 1 to 37.2% in Model 2 after including moderation variables. The contribution of this research provides practical implications for companies in designing optimal governance structures, for investors in assessing sustainability commitments, and for regulators in evaluating the implementation effectiveness of POJK No. 51/POJK.03/2017.